2017
DOI: 10.1016/j.jns.2017.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Acquired pendular nystagmus

Abstract: Acquired pendular nystagmus is comprised of quasi-sinusoidal oscillations of the eyes significantly affecting gaze holding and clarity of vision. The most common causes of acquired pendular nystagmus include demyelinating disorders such as multiple sclerosis and the syndrome of ocular palatal tremor. However, several other deficits, such as pharmacological intoxication, metabolic and genetic disorders, and granulomatous disorders can lead to syndromes mimicking acquired pendular nystagmus. Study of the kinemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 67 publications
(91 reference statements)
0
15
1
1
Order By: Relevance
“…The prevalence of the well-described pendular nystagmus 9,32 was exceedingly rare in our group, namely, at 0.5%. This one subject showed that this type of nystagmus can be a very distressing oculomotor finding in MS, with continuous visual complaints that interfere with daily activities.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The prevalence of the well-described pendular nystagmus 9,32 was exceedingly rare in our group, namely, at 0.5%. This one subject showed that this type of nystagmus can be a very distressing oculomotor finding in MS, with continuous visual complaints that interfere with daily activities.…”
Section: Discussioncontrasting
confidence: 52%
“…Well-known causes are pendular nystagmus and internuclear ophthalmoplegia. 3,[9][10][11] Furthermore, abnormalities of eye movements are associated with greater general disability in MS. 12,13 Hitherto, studies describing the extensive range of abnormalities were essentially based on clinical examination. 6,[14][15][16][17] It stands to reason that the clinical diagnosis of many eye movement disorders is difficult and can be challenging.…”
mentioning
confidence: 99%
“…Another barrier, especially in low-income countries (where telerehabilitation would be most needed), is the lack of technological infrastructure. A cross-sectional study (on 100 stroke survivors) in a Ghanaian outpatient neurology clinic demonstrated that 80%-93% of patients had a positive attitude toward telerehabilitation interventions; however, only 35% of them had smartphones [ 29 ]. Further development of telerehabilitation networks is essential to overcome these barriers [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, these oscillations remain unchanged in darkness when visual inputs have no influence on eye movements. Since the oscillations of APN are reset by large saccades, which produce a phase shift of the oscillation ( 22 ), it is more likely that APN originates within the neural integrator network in the brain stem and cerebellum ( 23 ). The premotor signal responsible for large saccades would basically reset the APN oscillations by silencing some neural integrator neurons that produce the nystagmus.…”
Section: Eye Movement Disorders In Msmentioning
confidence: 99%